Action of antimicrobial photodynamic therapy on heterotypic biofilm: Candida albicans and Bacillus atrophaeus - Silva, Michelle Peneluppi [UNESP] (2016)
The increase in survival and resistance of microorganisms organized in biofilms demonstrates the need for new studies to develop therapies able to break this barrier, such as photodynamic therapy, which is characterized as an alternative, effective, and non-invasive treatment. The objective was to evaluate in vitro the effect of antimicrobial photodynamic therapy on heterotypic biofilms of Candida albicans and Bacillus atrophaeus using rose bengal (12.5 μM) and light-emitting diode (LED) (532 nm and 16.2 J). We used standard strains of B. atrophaeus (ATCC 9372) and C. albicans (ATCC 18804). The biofilm was formed in the bottom of the plate for 48 h. For the photodynamic therapy (PDT) experimental groups, we added 100 μL of rose bengal with LED (P+L+), 100 μL of rose bengal without LED (P+L−), 100 μL of NaCl 0.9 % solution with LED (P−L+), and a control group without photosensitizer or LED (P−L−). The plates remained in agitation for 5 min (pre-irradiation) and were irradiated with LED for 3 min, and the biofilm was detached using an ultrasonic homogenizer for 30 s. Serial dilutions were plated in BHI agar and HiChrom agar and incubated at 37 °C/48 h. There was a reduction of 33.92 and 29.31 % of colony-forming units per milliliter (CFU/mL) for C. albicans and B. atrophaeus, respectively, from the control group to the group subjected to PDT. However, statistically significant differences were not observed among the P+L+, P+L−, P−L+, and P−L− groups. These results suggest that antimicrobial photodynamic therapy using rose bengal (12.5 μM) with a pre-irradiation period of 5 min and LED for 3 min was not enough to cause a significant reduction in the heterotypic biofilms of C. albicans and B. atrophaeus.